A positive association between the prevalence of circadian syndrome and overactive bladder in United States adults - Xiao, Yunfei; Yin, Shan; Wang, Jiahao; Cui, Jianwei; Yang, Zhenzhen; Wang, Jia; Bai, Yunjin (Frontiers in Public Health, 2023)
Objective: To explore the association between the prevalence of circadian syndrome (CircS) and overactive bladder (OAB).Cross-section analysis was based on the National Health and Nutrition Examination Survey 2005-2018. Data regarding OAB was collected from questionnaires. The association between the prevalence of CircS and OAB was elucidated using three multivariable logistic regression models. Stratified and interaction analyses were performed to find whether some factors can modify the association.Results: Totally 8,033 males and 8,065 females were included. People with CircS had a significantly higher prevalence of OAB compared to the non-CircS group in the fullyadjusted model (OR=1.238, 95%CI 1.080 to 1.419). A significant positive correlation between the number of CircS components and the prevalence of OAB was observed when the components were ≥6 (OR=1.975, 95%CI 1.463 to 2.665). No significant interaction was seen in the three models.There is a positive association between the prevalence of CircS and OAB.When the number of components is ≥6, the prevalence of OAB shows a strongly positive correlation with the number of CircS components.The same trend is also present in the correlation between the number of CircS components and the prevalence of OAB when the number of components is ≥6.